Relative Risk Estimation for Mycoplasma synoviae in Backyard Chickens in Paraguay - Suzuki, K.; Origlia, J.; Alvarez, F.; Faccioli, M.; Silva, M.; Caballero, J.; Nunez, L.; Castro, L. (International Journal of Poultry Science, 2009)
Poultry production is a growing industry in Paraguay, in southern South America. The insufficient farm management methods frequently applied in backyard chickens make them a possible reservoir for economically important diseases such as Mycoplasma synoviae that can influence commercial poultry operations. There are no former studies on a survey of Mycoplasma synoviae among backyard chickens in Paraguay. The objectives of this study were: (1) to observe the seroprevalence of MS in backyard chickens in Paraguay and (2) to generate maps for the estimated Relative Risk (RR) for MS in the study chickens, in place of using the observed seroprevalence. Paraguay is divided into 17 departments. A department-stratified random sampling was arranged and conducted. The required total sample size of 1537 from a chicken population of 17 million was sufficient to produce a 95% confidence interval with a desired precision of ±2.5% when the estimated seroprevalence was 50%. Sera were examined using a commercial indirect ELISA. The overall observed seroprevalence was 53%. The resulting maps for the estimated RR for Mycoplasma synoviae in the study chickens at department level were drawn. Departments with notably high or low disease risks were confirmed. Different types of epidemiological parameters can be calculated to take account of probable risk factors. Therefore, additional detailed investigations into those risk factors relating to Mycoplasma synoviae occurrence with respect to spatially epidemiological dissimilarities would be of interest.